2016
DOI: 10.12928/pharmaciana.v6i1.3043
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN KELOR (Moringa oleifera L.) TERHADAP AKTIVITAS ANALGESIK DAN ANTIINFLAMASI MELALUI EKSPRESI ENZIM SIKLOOKSIGENASE

Abstract: ABSTRAKKelor (Moringa oleifera L.) mengandung flavonoid sebagai zat berkhasiat utama. Kuersetin diketahui menghambat COX-2 pada proses inflamasi. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian ekstrak etanol daun kelor terhadap aktivitas analgesik dan antiinflamasi pada mencit. Studi analgesik dilakukan pada mencit pada dosis 12,5; 25 dan 50 mg/kgBB dengan metode geliat. Sedangkan aktivitas antiinflamasi dilakukan dengan pengukuran volume udem ekstrak etanol daun kelor pada dosis 35; 70 dan 140 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
3
0
5
Order By: Relevance
“…18 Another study conducted by Sulistyawati found that the ethanol extract of Moringa leaves orally could inhibit COX-2 expression at a dose of 140 mg/kg BW with anti-inflammatory power of 24.30±2.960% was able to reduce COX-2 expression 46.37±6.434% in mice. 19 Research by Arulselvan et al found that Moringa leaf extract could inhibit the expression of COX-2, iNOS, TNF-α, and IL-1-β in lipopolysaccharide-induced macrophages. 8 The results of the phytochemical analysis of the content of Moringa leaf extract (data not shown) in this study found the presence of tannin compounds but no flavonoid compounds.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another study conducted by Sulistyawati found that the ethanol extract of Moringa leaves orally could inhibit COX-2 expression at a dose of 140 mg/kg BW with anti-inflammatory power of 24.30±2.960% was able to reduce COX-2 expression 46.37±6.434% in mice. 19 Research by Arulselvan et al found that Moringa leaf extract could inhibit the expression of COX-2, iNOS, TNF-α, and IL-1-β in lipopolysaccharide-induced macrophages. 8 The results of the phytochemical analysis of the content of Moringa leaf extract (data not shown) in this study found the presence of tannin compounds but no flavonoid compounds.…”
Section: Discussionmentioning
confidence: 99%
“…13 98 contain flavonoids, whereas the n-hexane extract did not contain both alkaloids and flavonoids [18]. However, other study showed that the extract of Moringa leaves macerated in ethanol contained flavonoids and polyphenols [19]. The distilled water extract also contained steroids, triterpenoids, flavonoids, saponins, phenols, and tannins [12].…”
Section: Fig 3: Inhibition Zone Of Ethanol Extract (Upper Row) and Distilled Water Extract (Bottom Row)mentioning
confidence: 99%
“…(2) Ekstraksi senyawa aktif telah dilakukan pada daun kelor dengan menggunakan pelarut yang berbeda-beda. Hasil penelitian uji skrining fitokimia ekstrak daun kelor (3) menunjukkan bahwa ekstrak daun kelor dengan pelarut etanol metode maserasi mengandung senyawa flavonoid dan polifenol. Kedua senyawa tersebut telah dibuktikan secara kromatografi lapis tipis (KLT).…”
Section: Pendahuluanunclassified